Atlas of the world : The ultimate interactive atlas of the world - Jackson, Elaine (New York : Scholastic Inc., 2008)
This comprehensive, richly illustrated atlas takes you on an exciting globe-trotting adventure, continent by continent.
"Pop-ups, pull-tabs, wheels, flaps"
Includes index.
Basic Ed. Students
Keywords: Children's atlases; Physical geography -- Maps for children